The suitability of patient’s little finger diameter and middle finger lenght to the trachea diameter in predicting the tracheostomy cannula size: - - Fitria, Sova; -, Lily Setiani; Kurnia, Benny (Oto Rhino Laryngologica Indonesiana, 2025)
Background: A tracheostomy is a temporary or permanent opening of the trachea followed by a cannula insertion to secure the airway, a common life-saving procedure in otorhinolaryngology. However, tracheostomy cannula sizes vary significantly across manufacturers, with no standardized numbering system, complicating the selection of an appropriate size. The tracheal ring is made of cartilage, particularly in the fingers, is used as a marker for cartilage growth in the trachea. Purpose: This study aims to assess the suitability of little finger diameter and middle finger length to diameter of the trachea in order to predict the tracheostomy cannula size. Methode: This observational analytical study using a cross-sectional design, analyzing patients who underwent tracheostomy and met specific inclusion criteria. Measurements included the little finger diameter, middle finger length, and intraoperative anterolateral tracheal diameter. Data analysis was performed using Pearson and Spearman correlation tests. Result: Among 24 participants, adults accounted for 83.3% of cases, while children 16.7%, with a mean age of 54.5 years. The incidence of tracheostomy was more common in males (70.8%) and upper airway obstruction as the main indication (83,3%). The study identified a positive correlation between little finger diameter and tracheal internal diameter (r = 0.496, p < 0.05). Conversely, no significant correlation was observed between middle finger length and tracheal diameter (r = 0.318, p > 0.05). Conclusion: little finger diameter demonstrates potential as a predictor for tracheostomy cannula size, reflecting the internal tracheal diameter. Keywords: Tracheal diameter, little finger diameter, middle finger length, Tracheostomy cannula.